Japanese detail : - Hibi, Sadao (Chronicle Books, 1989)
Renowned for its tranquility and serenity, its simple, elegant lines, and harmonious use of natural forms, Japanese architecture is admired by designers, architects, and homeowners alike for its easy grace. Now with a striking new cover, Japanese Detail: Architecture surveys the essential elements of the Japanese aesthetic. From rough-hewn flagstone paths to the majestic lines of traditional roofs, from luminescent shoji screens and pristine paper walls to intricate latticework and ornate furnishings, this beautiful sourcebook draws together all the exquisite details of a style that is as timeless as it is contemporary.